Voluntary musical imagery in music practice: contextual meaning, neuroscientific mechanisms and practical applications - Meng, Chen; Luck, Geoff (Frontiers in Psychology, 2024)
Practice is acknowledged as a crucial facilitator for musicians to achieve performance excellence. Despite the rich literature on incorporating musical imagery intentionally to improve one’s practice efficacy, limitations remain in the understanding of voluntary musical imagery (VMI) in the context of musical practice. Therefore, our aims in this review are threefold. First, we enriched the interpretation of VMI in the context of music practice through the lens of embodied cognition. Second, we integrated neuroscientific findings to elucidate how the deliberate use of musical imagery parallels physical practice in effectiveness. Third, we synthesize work on the application of VMI in enhancing musical learning from both theoretical and practical perspectives. By providing an integrated overview of voluntary musical imagery, we highlight gaps in the literature and encourage further research on (1) the impact of embodied experiences on VMI formation, (2) optimal imagery content and ratio combination to establish a personalized intervention protocol for more effective musical pedagogy, and (3) on physiological measures to access VMI effectiveness. Additionally, we highlight the crucial implications of VMI for researchers, performers, and music educators.